Expression and Immunogenicity of Recombinant African Swine Fever Virus Proteins Using the Semliki Forest Virus - Fang, Niran; Yang, Bin; Xu, Ting; Li, Yanpeng; Li, Huimin; Zheng, Hanghui; Zhang, Aiguo; Chen, Ruiai (Frontiers in Veterinary Science, 2022)
African swine fever virus (ASFV) is a large DNA virus belonging to the Asfarviridae family that damages the immune system of pigs, resulting in the death or slaughter of millions of animals worldwide. Recent modern techniques in ASFV vaccination have highlighted the potential of viral replicon particles (RPs), which can efficiently express foreign proteins and induce robust cellular and humoral immune responses compared with the existing vaccines. In this study, we established a Semliki Forest virus (SFV) vector by producing replication-defective viral particles. This vector was used to deliver RPs expressing ASFV antigens. SFV-RPs expressing ASFV p32 (SFV-p32) and p54 (SFV-p54) were tested in baby hamster kidney (BHK-21) cells. Proteins expression was evaluated via western blotting and indirect immunofluorescence, while immunogenicity was evaluated in BALB/c mice. The resulting RPs exhibited high levels of protein expression and elicited robust humoral and cellular immune responses. Keywords: African swine fever virus, Semliki Forest virus, replication-defective viral particles, immunogenicity, cellular immune response.